PENGGUNAAN SISTEM PEMBAYARAN E-MONEY BERBASIS SERVER UNTUK MENDUKUNG GERAKAN CASHLESS SOCIETY PADA GENERASI MILENIAL - Dwijayanti, Ni Made Ayu; Mariani, Wayan Eny; Utami, Ni Made Mega Abdi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
This study aims to find out how to use a Server Based E-Money Payment System to Support the Cashless Society Movement in the millennial generation in the DIV Managerial Accounting Program at the Bali State Polytechnic. Associative quantitative methods are used to describe this phenomenon, through survey data collection in the form of questionnaires distributed by Google. forms. The sampling technique used was purposive sampling. Sample obtained as many as 110 respondents. The indicators used to see the perception of the millennial generation on the use of e-wallet are the perception of convenience, the perception of benefits and the perception of risk. The existing data is then processed and interpreted more deeply so that conclusions can be drawn. The results show that the perception of the ease of using server-based electronic money has no effect on supporting a cashless society, but the perception of benefits is proven to have an effect on supporting a cashless society, while the perceived risk of using server-based electronic money has no effect on supporting the cashless society movement.